DETERMINASI KADAR LOGAM TIMBAL (Pb) DALAM MAKANAN KALENG MENGGUNAKAN DESTRUKSI BASAH DAN DESTRUKSI KERING - Dewi, Diana Candra (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2012)
Lead (Pb) is pollutant found in canned foods. It is derived from the soldering between the can and the lid. This study aims to find out the analytical performance of standar curves , the better method between dry ashing dan wet ashing, the best oxidant solution in wet ashing ang determine lead in canned sausage and canned lychee.This research including : Performance determination of the standard addition curve analysis includes linearity, limits of detection and limits of quantitation, sensitivity, accuracy and precision, sample destruction using dry ash 500 oC and wet destruction with a variety of oxidizing subtrace such as HNO3 p.a; HNO3 p.a, H2SO4 p.a (3:1), and HNO3 p.a, H2SO4 p.a, H2O2 p.a (6:2:1), and determine the concentration of lead in canned sausage and canned lycheeThe results of this research of the standard curve analysis of lead (Pb) are r =0,9999, LOD 0,028 ppm, LOQ 0,0933 ppm, and sensitivity of 0,00757 the average accuracy of 98%, and precision 2,74%. Wet ashing is more stabil than dry ashing. The best oxidizing substance of canned sausage comes from HNO3, H2SO4 and H2O2 (6:2:1) and lead was found 0,64 ppm whilebest oxidizing substance of canned lychee comes from HNO3, H2SO4 (3:1) and lead was found 0,72 ppm.